Investigating star-formation activity towards the southern H ii region RCW 42. Issue 4 (29th July 2022) - Kumar, Vipin; Vig, S; Veena, V S; Mohan, S; Ghosh, S K; Tej, A; Ojha, D K
ABSTRACT: The star-forming activity in the H ii region RCW 42 is investigated using multiple wavebands, from near-infrared to radio wavelengths. Located at a distance of 5.8 kpc, this southern region has a bolometric luminosity of 1.8 × 10 6 L⊙ . The ionized gas emission has been imaged at low radio frequencies of 610 and 1280 MHz using the Giant Metrewave Radio Telescope, India, and shows a large expanse of the H ii region, spanning 20 × 15 pc 2 . The average electron number density in the region is estimated to be ∼70 cm −3, which suggests an average ionization fraction of the cloud to be 11 % . An extended green object EGO G274.0649-01.1460 and several young stellar objects have been identified in the region using data from the 2MASS and Spitzer surveys. The dust emission from the associated molecular cloud is probed using Herschel Space Telescope, which reveals the presence of five clumps, C1-C5, in this region. Two millimetre emission cores of masses 380 and 390 M⊙ towards the radio emission peak have been identified towards C1 from the ALMA map at 1.4 mm. The clumps are investigated for their evolutionary stages based on association with various star-formation tracers, and we find that all the clumps are in active/evolved stage.